2000
DOI: 10.1074/jbc.m909267199
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Transcription Factor TGA2.2 Is the Main Component of as-1-binding Factor ASF-1 and Is Involved in Salicylic Acid- and Auxin-inducible Expression of as-1-containing Target Promoters

Abstract: TGA2.2 is a major component of either complex, asshown by supershift analysis and Western blot analysis of DNA affinity-purified SARP. Minor amounts of a protein immunologically related to TGA2.1 were detected, whereas TGA1a was not detectable. Overexpression of either TGA2.2 or a dominant negative TGA2.2 mutant affected both SA and auxin (2,4D) inducibility of various target promoters encoding as-1-like elements, albeit to different extents. This indicates that TGA2.2 is a component of the enhancosome assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
0
29

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(166 citation statements)
references
References 48 publications
6
131
0
29
Order By: Relevance
“…It has been shown that salicylic acid and auxins can induce plant genes through the interaction of inducible transcription factors with the as-1-related ciselements (Chen and Singh, 1999;Niggeweg et al, 2000). The Tnt1C sequence analyzed here contains a nearly palindromic sequence within the U3 region that closely resembles the as-1 element (TGACGTCAnnnnTGACGTCA), and this could be important for the induction of this Tnt1 subfamily by auxins and SA.…”
Section: The U3 Regions Of the Three Tnt1 Subfamilies Contain Promotementioning
confidence: 98%
See 1 more Smart Citation
“…It has been shown that salicylic acid and auxins can induce plant genes through the interaction of inducible transcription factors with the as-1-related ciselements (Chen and Singh, 1999;Niggeweg et al, 2000). The Tnt1C sequence analyzed here contains a nearly palindromic sequence within the U3 region that closely resembles the as-1 element (TGACGTCAnnnnTGACGTCA), and this could be important for the induction of this Tnt1 subfamily by auxins and SA.…”
Section: The U3 Regions Of the Three Tnt1 Subfamilies Contain Promotementioning
confidence: 98%
“…It has been already shown that salicylic acid and 2,4-D can induce plant gene expression through as-1-related elements (Chen and Singh, 1999;Niggeweg et al, 2000). It is interesting that although sequence variability among the Tnt1C sequences amplified is high and two different subfamilies can be defined, all of them maintain a consensus as-1-related element within the U3 region.…”
Section: Retrotransposons As Models To Analyze Stressassociated Exprementioning
confidence: 99%
“…Transgenic plants overexpressing these TGA mutants showed different phenotypes. In one study, overexpression of a tobacco TGA2.2 mutant (a homolog of Arabidopsis TGA2 ) diminished SA-and auxininducible PR gene induction (Niggeweg et al, 2000a). In another study, in which an Arabidopsis TGA2 mutant was overexpressed, PR gene induction was enhanced further (Pontier et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Higher affinity binding to the Z-BACϩ of a class I TGA-type bZIP protein, PvTGA1.1, compared with two class II proteins, PvTGA2.1 and PvTGA2.2 (Fig. 4), is in contrast to that for the as-1 element that favors binding of a class II protein (Niggeweg et al, 2000a). High-affinity binding of class I compared with class II proteins may be an important difference between the Z-BAC and as-1 elements that is also manifested in a difference in the AZ-specific and auxin-regulated expression of the Z-BAC element (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…A major component of the ASF-1-binding factor that binds to the as-1 element ) is a TGA-type class II bZIP protein (Niggeweg et al, 2000a). Higher affinity binding to the Z-BACϩ of a class I TGA-type bZIP protein, PvTGA1.1, compared with two class II proteins, PvTGA2.1 and PvTGA2.2 (Fig.…”
Section: Discussionmentioning
confidence: 99%